2018
DOI: 10.3389/fvets.2018.00238
|View full text |Cite
|
Sign up to set email alerts
|

Serological Prevalence of Contagious Bovine Pleuropneumonia in Niger in 2017

Abstract: Contagious bovine pleuropneumonia (CBPP) is a highly contagious disease of cattle caused by Mycoplasma mycoides subsp. mycoides Biotype Small Colony (MmmSC). The disease currently occurs in most of sub-Saharan Africa and where it is endemic and a major constraint for improving pastoral productivity. Following the persistence of this scourge, and in order to control this disease, a serological survey was conducted to determine the prevalence of CBPP in Niger. In fact, 1,590 sera were collected following a strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Coupled with inadequate resources, few samples were therefore collected for laboratory diagnosis. In addition, the veterinary pharmaceutical supply chain (Yansambou et al, 2018) was not efficient. With time, the DVS capacity improved greatly and each region in the NCR had two veterinarians with para-veterinary supporting staff which improved CBPP and other livestock disease diagnoses and reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with inadequate resources, few samples were therefore collected for laboratory diagnosis. In addition, the veterinary pharmaceutical supply chain (Yansambou et al, 2018) was not efficient. With time, the DVS capacity improved greatly and each region in the NCR had two veterinarians with para-veterinary supporting staff which improved CBPP and other livestock disease diagnoses and reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Previously second only to rinderpest as the disease of prime concern in cattle, CBPP remains a significant concern and threat to the livestock industry [243,244]. Following drastic stamping out efforts, CBPP was eradicated in the 20th century from most of the world but continues to plague Sub-Saharan Africa [245][246][247][248][249][250][251][252].…”
Section: Contagious Bovine Pleuropneumoniamentioning
confidence: 99%
“…CBPP is one of the major diseases of cattle that causes significant losses to both the local and national economy. The serological survey of CBPP in the region of Niamey out of the eight regions of Niger country using c‐ELISA revealed an individual seroprevalence of 6.8% (Yansambou, Ferreira, et al., 2018). Furthermore, CBPP endemic situation was confirmed by a seroprevalence study conducted in all regions of the country, revealed an individual prevalence of 4.15% (Yansambou, Diallo, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The serological survey of CBPP in the region of Niamey out of the eight regions of Niger country using c‐ELISA revealed an individual seroprevalence of 6.8% (Yansambou, Ferreira, et al., 2018). Furthermore, CBPP endemic situation was confirmed by a seroprevalence study conducted in all regions of the country, revealed an individual prevalence of 4.15% (Yansambou, Diallo, et al., 2018). To reduce the impact of this disease, the government of Niger has implemented an annual policy of free vaccination.…”
Section: Introductionmentioning
confidence: 99%